Photodynamic therapy with Curcuma longa for the treatment of Kerion celsi - Tânia Aparecida Meneghel; Daniella de Grande Curi (Sociedade Brasileira de Dermatologia (SBD), 2023)
Kerion Celsi is an inflammatory variant of tinea capitis and is usually caused by Microsporum canis. Griseofulvin is the gold standard treatment, but FDA approves its use only for children up to two years. Even though it is rare in children younger than three years, tinea capitis can still occur, as in the case of the one-year-old child who was successfully treated with photodynamic therapy combined with curcumin, resulting in total remission.